An N‐Heterocyclic‐Carbene‐Derived Distonic Radical Cation. Issue 10 (30th January 2020) - Gallagher, Nolan M.; Ye, Hong‐Zhou; Feng, Shuting; Lopez, Jeffrey; Zhu, Yun Guang; Van Voorhis, Troy; Shao‐Horn, Yang; Johnson, Jeremiah A.
Abstract: We present the discovery of a novel radical cation formed through one‐electron oxidation of an N‐heterocyclic carbene–carbodiimide (NHC–CDI) zwitterionic adduct. This compound possesses a distonic electronic structure (spatially separate spin and charge regions) and displays persistence under ambient conditions. We demonstrate its application in a redox‐flow battery exhibiting minimal voltage hysteresis, a flat voltage plateau, high Coulombic efficiency, and no performance decay for at least 100 cycles. The chemical tunability of NHCs and CDIs suggests that this approach could provide a general entry to redox‐active NHC–CDI adducts and their persistent radical ions for various applications. Abstract : A persistent distonic radical cation was prepared through one‐electron oxidation of an N‐heterocyclic carbene–carbodiimide (NHC–CDI) adduct bearing pyrene substituents. Application of this compound in an organic redox‐flow battery was demonstrated, setting the stage for the development of novel redox‐active NHC–CDIs for various applications.